Analisis Bahasa Gender dalam Fatwa tentang â€œMusawat Al Marâ€™ah bi Al Rajulâ€ Oleh: Ahmad Al-Shurbasy dalam Kitab â€œYasâ€™alunak fi al-Din wa al-Hayatâ€ - Muhammad Afthon Ulin Nuha (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Gender issues are now in the great spotlight in the eyes of the wider community. Gender is generally identified as the difference between men and women from a socio-cultural perspective. Gender in general can be defined as a cultural concept that distinguishes between men and women from a socio-cultural perspective that can change according to changing times. Apart from that, gender issues regarding the roles between men and women in society are based on socio-cultural constructions and the history of society, not solely because of biological, anatomical or sexual aspects. Departing from this problem the author considers it necessary to express thoughts about Gender Language in the Fatwa about the text